Membaca Arah Politik Hukum Indonesia: Telaah Kritis Terhadap Logika Pembentukan Hukum Nasional - Thessa Nada Lorenza; Ardian Mulyadi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study examines the direction of Indonesia's legal politics through a critical analysis of the logic behind national law-making, referencing the perspectives of Mahfud MD and Satjipto Rahardjo's progressive legal theory. Using a normative-juridical approach and qualitative analysis, the research explores the relationship between legal politics, constitutionalism, and substantive justice in legislative practices. The findings reveal that the formation of national law often involves a tug-of-war between constitutional idealism and the pragmatic interests of power, leading to a distortion of justice values. Mahfud MD’s perspective emphasizes the importance of aligning legal politics with Pancasila and the constitution, while Satjipto Rahardjo’s progressive law advocates for a participatory, adaptive, and pro-people approach. This study recommends participatory, transparent, and accountable legislative reforms to restore the function of law as an instrument of social justice and sustainable social transformation.